2019
DOI: 10.3390/app9214575
|View full text |Cite
|
Sign up to set email alerts
|

Self-Piercing Riveted Joint of Vibration-Damping Steel and Aluminum Alloy

Abstract: In this study, the self-piercing rivet (SPR) joining of vibration-damping steel and aluminum alloy (Al5052-H32) is successfully carried out, for the first time to our knowledge, and the effects of die type and joint configuration on the mechanical performance, failure mode, and geometrical characteristics of the new joint are investigated. The vibration-damping steel and Al5052-H32 SPR joint exhibits the largest tensile–shear load when a flat die is used. An increase in the die taper angle and diameter decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…The interlock is critical for the mechanical strengths and failure behaviours of SPR joints. Too small interlock values may result in pull-out failure of the rivet shank from the bottom sheet [9]. The Tmin is very important for the corrosion resistance and water-proof performance of SPR joints.…”
Section: Introductionmentioning
confidence: 99%
“…The interlock is critical for the mechanical strengths and failure behaviours of SPR joints. Too small interlock values may result in pull-out failure of the rivet shank from the bottom sheet [9]. The Tmin is very important for the corrosion resistance and water-proof performance of SPR joints.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al 14) demonstrated the joinability of aluminum alloys with different gauges to mild steel sheets. Kam et al 15) illustrated the feasibility of SPR joints between vibration-damping steel (consisting of two steel sheets separated by a viscoelastic adhesive polymer layer) and an aluminum alloy. Zhang et al 16) observed that the strength of the steel significantly influenced the strength of steel/aluminum SPR joints.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors [ 10 , 12 ] carried out fatigue and static strength on cross-shaped SFR joints with aluminum alloy plates at various loading angles. Kam et al [ 13 ] reported the type of effect of die type and joint configuration on mechanical performance, failure mode, and geometrical characteristics on SPR joints of steel and aluminum alloy. The SPR joint between dissimilar material combinations was also experimentally studied by Taek-Eon Jeong and Xiaocong He [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%